Sugeno Fuzzy for Non-Playable Character Behaviors in a 2D Platformer Game - Rismanto, Ridwan; Ariyanto, Rudy; Setiawan, Awan; Elinggar Zari, Melcinsiasih (International Journal of Engineering and Technology, 2018)
One aspect for a platformer game to be challenging to play is the NPC (Non Playable Character). An NPC is often placed as an obstacle for player to finish at each level. However, an effort must be done to create a behavior of an NPC to be challenging enough and not monotonous. Creating random behavior is one way. But the problem with this approach is a less interactive NPC behavior because of its inability to respond from the game state accordingly. In this paper, we propose an implementation of Sugeno Fuzzy to create behaviors for the NPCs. This methodology takes playerâ€™s state and NPCâ€™s state to determine what action will be done. The inputs are player to NPC distance, NPCâ€™s health and playerâ€™s weapon ammunition. The outputs are retreat, defense and attack. We applied this methodology in an educational game about Rubela virus vaccination â€œHealthy Heroâ€ for its boss enemies. Evaluation shows that by applying Sugeno Fuzzy, the NPC behavior can responds to playerâ€™s state and its own state. The real-time execution resulted in 100% correct behavior according to the predefined rules, therefore increasing the behavior interactivity for the NPC.Â